Implementasi Fatwa MUI No 3 Tahun 2003 tentang Zakat Penghasilan dan Ijtihad Yusuf Al-Qaradhawi dalam Pembayaran Zakat Penghasilan oleh Pemain Esports - Nadya Salsabila; Panji Adam Agus Putra; Ira Siti Rohmah Maulida (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. The profession of Muslims is growing, one of which is eSports, but this income zakat is a new case in Islamic Law. Because there are no strict rules from the Quran and Hadith. Regarding this issue, there is a problem of differences of opinion between the MUI Fatwa and Yusuf Al-Qaradhawi regarding income zakat. The purpose of this study is to find out the similarities and differences in income zakat from the two opinions of ijtihad used the similarities and differences from the two views implemented in the payment of income zakat by eSports players. This research method uses a qualitative approach using comparative studies. The type of writing of literature studies and primary data sources is interviews and secondary data obtained from journals, etc. As a result, the similarities are in the level of zakat, the difference between nishab and haul. The equation of ijtihad uses the bayani method using QS. Al-Baqarah verse 267. The difference is in qiyas, where Yusuf Qaradhawi uses Qiyas Syabah and uses a combination of intiqa'i and insya'i, and the MUI Fatwa uses intiqa'i. For eSports players, it is included in income zakat and there is no element that prohibits it, those who have the right to issue zakat are RF and ECP, for RHW and FG it is not zakat because it has not reached its nishab. Abstrak. Profesi umat Muslim yang berkembang, salah satunya adalah eSports, namun zakat penghasilan ini merupakan kasus baru dalam Hukum Islam. Sebab tidak ada aturan yang tegas dari Quran dan Hadis. Mengenai masalah ini terdapat permasalahan adanya perbedaan pandangan antara Fatwa MUI dan Yusuf Al-Qaradhawi mengenai zakat penghasilan. Tujuan penelitian ini untuk mengetahui persamaan dan perbedaan zakat penghasilan dari kedua pendapat daan ijtihad yang digunakan persamaan dan perbedaanya dari kedua pandangan yang diimplementasikan pada pembayaran zakat penghasilan oleh pemain eSports. Metode penelitian ini menggunakan pendekatan kualitatif dengan menggunakan studi komparatif. Jenis penulisan studi pustaka dan sumber data primer yaitu wawancara dan sekunder diperoleh dari jurnal,dll. Hasilnya persamaannya ada pada kadar zakat, perbedaan nishab dan haul. Persamaan ijtihadnya menggunakan metode bayani dengan menggunakan QS. Al-Baqarah ayat 267. Perbedaan pada qiyas, dimana Yusuf Qaradhawi menggunakan Qiyas Syabah dan memakai gabungan intiqa’i dan insya’i, dan Fatwa MUI mengggunakan intiqa’i. Untuk pemain eSports termasuk dalam zakat penghasilan dan tidak ada unsur yang mengharamkanya, yang berhak mengeluarkan zakat adalah RF dan ECP, untuk RHW dan FG tidak zakat karena belum mencapai nishabnya.